2021
DOI: 10.1590/1982-4327e3109
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Teacher Self-Efficacy in Teacher Education for Inclusive Practices

Abstract: Self-efficacy concerns the individual’s beliefs in their ability to perform certain activities and influences the level of determination and effort involved. This study aimed to investigate whether teacher education courses for inclusive practices, involving sources of self-efficacy, produce effects on teacher self-efficacy. Thirty-six teachers participated; part of them took part in the course on inclusion of students with intellectual disabilities and the others on inclusion of students with giftedness. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
0
0
4
Order By: Relevance
“…The findings confirmed the first research hypothesis, suggesting that TEIP was positively associated with autonomous motivation. Consistent with previous studies [ 10 , 11 , 12 , 40 , 41 ], the results indicated that teachers who feel able to implement inclusive teaching strategies are more involved in the activities they carry out because they are intrinsically motivated. Furthermore, this finding is consistent with SDT which suggests that the desire to feel effective and competent contributes to the development of autonomous motivation [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…The findings confirmed the first research hypothesis, suggesting that TEIP was positively associated with autonomous motivation. Consistent with previous studies [ 10 , 11 , 12 , 40 , 41 ], the results indicated that teachers who feel able to implement inclusive teaching strategies are more involved in the activities they carry out because they are intrinsically motivated. Furthermore, this finding is consistent with SDT which suggests that the desire to feel effective and competent contributes to the development of autonomous motivation [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Guru tersebut menyatakan bahwa meskipun minim pengalaman dan pengetahuan, namun memiliki rasa percaya diri yang tinggi dan tidak mudah menyerah akan meningkatkan nilai efektivitas seseorang. Hasil penelitian ini sesuai dengan penelitian terdahulu yang pernah dilakukan oleh San Martin et al (2021), Sari et al (2009), dan Martins & Chacon (2021) yang menunjukkan bahwa efikasi diri guru berdampak pada praktik pendidikan inklusif. Berdasarkan yang telah diuraikan di atas sejalan dengan penelitian terdahulu, maka dapat disimpulkan bahwa efikasi diri guru TK berdampak pada praktik pendidikan inklusif di sekolah inklusi.…”
Section: Hasil Dan Pembahasanunclassified
“…Assim, entendemos que a autoeficácia docente também é contextual ao fazer docente, sendo importante identificá-la conforme os objetivos específicos de cada demanda da sala de aula. A seguir, apresentaremos estudos nacionais e internacionais que abordam a autoeficácia docente para práticas inclusivas (MARTINS; CHACON, 2021;NINA et al, 2022;YADA et al, 2022) e a autoeficácia com alunos com TEA (RUBLE; USHER; MCGREW, 2011;BOSA, 2015;LOVE et al, 2020;LOPES et al, 2021).…”
Section: Autoeficácia Docenteunclassified
“…Os estudos até aqui apontados evidenciam que são necessárias mais pesquisas para auxiliar na compreensão sobre como a crença do professor nas suas capacidades para ensinar alunos com TEA pode promover intervenções mais eficazes; e como maior apoio e mais conhecimento podem aprimorar a experiência educacional dessas crianças. Além disso, é necessário levar em consideração as quatro diferentes fontes de autoeficáciaexperiência de domínio, experiência vicária, persuasão verbal e estado afetivo (BANDURA, 1997) como uma maneira de ampliar e melhorar a autoeficácia dos professores, criando possibilidades de capacitação em que eles possam usufruir de experiências positivas e bem-sucedidas em práticas inclusivas e com alunos com TEA (LOVE et al2020;CHACON, 2021;YADA et al2022). e 42,1% possuem algum tipo (N=32), mas não especificaram o tipo nem a carga horária.…”
Section: Autoeficácia De Professores De Alunos Com Teaunclassified
See 1 more Smart Citation